Commodity price shocks and the gender wage gap: Evidence from the metal mining prices super-cycle in Chile (2022)
This paper analyzes the local impact of a natural resource shock on female and male wages as well as the gender wage gap. We contrast three hypotheses using the Dutch disease theory and gender-based segregation patterns in the labor market. Using household level data aggregated at a municipality-level from 2000 to 2015, we examine the case of Chile that was exposed to the Metal Mining Prices Super-Cycle between 2003 and 2011. We exploit the spatial heterogeneity in the exposure to the shock, and find a positive and significant impact on wages for both men and women. We also provide evidence of a significant reduction in the gender wage gap in municipalities more exposed to the commodity shock in comparison to municipalities with less exposure. In addition, we use spatial econometric specifications and find evidence suggesting the existence of spatial spillovers between neighboring municipalities